أثر التمكين الإداري في الإبداع الإداري: دراسة ميدانية على عينة من المصارف السودانية - الماحي، محمد الأمين أحمد (جامعة دنقلا - كلية الآداب والدراسات الإنسانية, 2020)
هدفت هذه الدراسة إلى التعرف على أثر التمكين على الإبداع الإداري في القطاع المصرفي السوداني مستهدفة بذلك المصارف العاملة بولاية القضارف، ولتحقيق أهداف الدارسة تم استخدام المنهج الوصفي التحليلي، حيث صممت استبانة لجمع البيانات وتوزعت على (100) موظف في (22 مصرف) من مجموع الموظفين البالغ عددهم (102) موظفا، تم استرجاع (96) استبانة بنسبة 94%، وبعد المعالجة الإحصائية اعتمادا على نظام الـ(SPSS 24) توصلت الدراسة إلى عدة نتائج أهمها وجود أثر معنوي للتمكين الإداري على الإبداع الإداري مقداره 35%، كما يؤثر تفويض الصلاحيات في الإبداع الإداري للعاملين في المصارف السودانية بنسبة 40%، تؤثر فاعلية الاتصال في الإبداع الإداري للعاملين بنسبة 70%، ويؤثر تحفيز العاملين في الإبداع الإداري للعاملين بمقدار 74%، كما يؤثر التدريب في الإبداع الإداري للعاملين في المصارف السودانية بنسبة 63%، كما أوضحت الدراسة أنه لا توجد فروق في مستويات الإبداع مردها للمستوى الوظيفي. وأوصت الدراسة بتعزيز الممارسات الإدارية التي تدفع بفاعلية الاتصال الإداري والتدريب الهادف ومنح العاملين المزيد من الصلاحيات من خلال التفويض. This study aimed at identifying the impact of empowerment on administrative innovation in the Sudanese banking sector, targeting banks working in Al Qadarif state. To achieve the goals of the study, the descriptive and analytical approach was used, and a questionnaire to collect data was designed and handed out to 80 employees in 22 banks. From the total number of 102 employees, 75 questionnaires (94%) were recovered. After statistical treatment based on SPSS 24 system, the study has reached several results, the most important of which is that administrative empowerment has an impact on morale which affects administrative innovation by 35%, delegation of authorities also affects administrative innovation for those working in Sudanese banks by 40%, efficiency of communication by 70%, incentives by 74%, and training by 63%. The study also showed that while there were innovation levels differences due to position level, there are no differences in administrative empowerment and innovation levels attributed to variables of (gender, qualification, years of experience or the bank type). The study recommended promotion of administrative practices that enhance the efficiency of administrative communication, purposeful training and working on giving more authorities through administrative delegation.
Keywords: التنمية الإدارية -- التمكين الإداري -- الابتكار الإداري -- الموارد البشرية -- البنوك السودانية